Organic substrates effect in strawberry cv´Albion´ (Fragaria sp.) plants, under field conditions (2016)
The strawberiy crop is one of the production options for farmers, mainly in the departments of Cundinamarca, Antioquia and Boyaca. The increasingly open world trade growing trend towards agricultura determines that national agricultural activities should be more productive and competitive every day, it supported these new and improved production technologies. Within these substrates using different order to solve problems like acidity, high erosion or phytosanitary problems that prevent direct sowing in the soil is counted. Given the above, the objective of the research was the evaluation of different organic substrates in the growth and development of strawberry plants cv ’Albion’, under field conditions. Was used for evaluation as a completely randomized design with three treatments being S1: soil 50% + coir 50% (S: FC), S2: soil 50% + rice husk 25% + coir 25% (S: FC: CA) and S3: soil 50% + 50% rice hull (5:CA), each with three replications conto. The variables evaluated were fresh and dry root mass and aerial part, leaf area, total chlorophylls, number of fruits/plant and production g/plant. Treatment (S1), showed significant differences according to Tukey test (P S 0.05) in most parameters assessed, this makes for an alternative for the production of strawberry cv ’Albion’ under the study conditions.